2010
DOI: 10.1111/j.1532-7795.2010.00699.x
|View full text |Cite
|
Sign up to set email alerts
|

The Enduring Significance of Racism: Discrimination and Delinquency Among Black American Youth

Abstract: Prominent explanations of the overrepresentation of Black Americans in criminal justice statistics focus on the effects of neighborhood concentrated disadvantage, racial isolation, and social disorganization. We suggest that perceived personal discrimination is an important but frequently neglected complement to these factors. We test this hypothesis with longitudinal data on involvement in general and violent juvenile delinquency in a sample of Black youth from a variety of communities in 2 states. We examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
94
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(102 citation statements)
references
References 53 publications
8
94
0
Order By: Relevance
“…The stresses created by the experience of racial aggressions and microaggressions can embed in a child. They can affect children's and adolescents' perceptions of themselves and others and how they deal with what they feel and experience (e.g., Martin et al, 2011). Still, many children and their families demonstrate instrumental and psychological resilience by building on individual, family, and cultural strengths (Spencer, 2007).…”
Section: Racismmentioning
confidence: 99%
See 1 more Smart Citation
“…The stresses created by the experience of racial aggressions and microaggressions can embed in a child. They can affect children's and adolescents' perceptions of themselves and others and how they deal with what they feel and experience (e.g., Martin et al, 2011). Still, many children and their families demonstrate instrumental and psychological resilience by building on individual, family, and cultural strengths (Spencer, 2007).…”
Section: Racismmentioning
confidence: 99%
“…Children (and adults) adapt to hostile environments in ways that can undermine learning and support their involvement in unhealthy or high-risk behaviors (Crick & Dodge, 1994;Martin et al, 2011). However, the principles developed in the companion article on malleability and plasticity suggest the power of developmentally constructive environments to promote resilience as well as positive developmental and learning outcomes (e.g., Masten & Coatsworth, 1998).…”
Section: Intergenerational Transmission Of Adversity and Assetsmentioning
confidence: 99%
“…Although a few studies include both sexes (e.g. Martin et al, 2011;Simons et al, 2003), at present no study has examined these processes among a sample of females. Addressing this gap is important given the fact not only that African American females deserve attention in their own right as worthy objects of study, but that evidence suggests that racial discrimination is gendered and therefore may gender behavioral responses (e.g.…”
mentioning
confidence: 96%
“…At least 13 recent studies document a link between individual experiences with racial discrimination and concurrent or subsequent offending. These studies find that interpersonal racial discrimination is associated with self-reported conduct problems (Brody, et al, 2006;DuBois, Burk-Braxton, Swenson, Tevendale, & Hardesty, 2002;Nyborg & Curry, 2003;Simons & Burt, 2011;Simons et al, 2003), violence (Caldwell, Kohn-Wood, Schmeelk-Cone, Chavous, & Zimmerman, 2004;Simons, Simons, & Burt, 2006;Stewart & Simons, 2006), delinquency (Burt et al, 2012;Martin, et al, 2011;Unnever, Cullen, Mathers, McClure, & Allison, 2009), and official reports of arrest (McCord & Ensminger, 1997. A number of different measures of discrimination are used, but all ask the respondents to report whether they have experienced one or more negative acts because, from their perspective, they are black.…”
mentioning
confidence: 96%
“…Another limitation of the Connell et al study was that race/ethnicity was not included as a covariate in the analysis because Caucasian youth constituted 83% of the sample. This nonrepresentative sample was especially problematic because both research and crime statistics indicate Black youth have an elevated risk of illegal behaviors (Franke, 2000;Martin et al, 2011).…”
Section: Peers and Social Learning Theorymentioning
confidence: 99%